Load Forecasting Analysis by Time Series Method - S, Kuldeep; G S, Anitha (International Journal of Engineering and Technology, 2018)
Load forecasting is a very important factor for designing power systems. A good knowledge of load pattern and behavior is very important for proper coordination, design and economic operation. Though a lot of research has been done on load forecasting, there are many tools and methods still being developed to accurately predict load behavior. This paper does an analysis of sample load data and predicts the next instant load using feedforward time series neural network model